The Spirit Model: Sales Performance through Individual Realization, Impact, and Transformation - Hart Garrett (Scientific Bulletin)
Sales organizations face persistent challenges in aligning employee engagement, retention, and performance with organizational objectives. The Sales Performance through Individual Realization, Impact, and Transformation (SPIRIT) model introduces a conceptual framework integrating self-determination theory and leader-member exchange to combine individual autonomy with relational support to address deficiencies in sales leadership. The model's components – individual realization, impact, and transformation – operationalize leadership practices through targeted interventions, feedback systems, and technology integration. While untested, SPIRIT provides a theoretical contribution to understanding the interplay between intrinsic motivation and relational dynamics to create a foundation for future empirical studies.